Revision of Tympanopleura Eigenmann (Siluriformes: Auchenipteridae) with description of two new species - Walsh,Stephen J. (2015)
The Neotropical catfish genus Tympanopleura, previously synonymized within Ageneiosus, is revalidated and included species are reviewed. Six species are recognized, two of which are described as new. Tympanopleura is distinguished from Ageneiosus by having an enlarged gas bladder not strongly encapsulated in bone; a prominent pseudotympanum consisting of an area on the side of the body devoid of epaxial musculature where the gas bladder contacts the internal coelomic wall; short, blunt head without greatly elongated jaws; and smaller adult body size. Species of Tympanopleura are distinguished from each other on the basis of unique meristic, morphometric, and pigmentation differences. Ageneiosus melanopogon and Tympanopleura nigricollis are junior synonyms of Tympanopleura atronasus. Tympanopleura alta is a junior synonym of Tympanopleura brevis. A lectotype is designated for T. brevis. Ageneiosus madeirensis is a junior synonym of Tympanopleura rondoni. Tympanopleura atronasus, T. brevis, T. longipinna, and T. rondoni are relatively widespread in the middle and upper Amazon River basin. Tympanopleura cryptica is described from relatively few specimens collected in the upper portion of the Amazon River basin in Peru and the middle portion of that basin in Brazil. Tympanopleura piperata is distributed in the upper and middle Amazon River basin, as well as in the Essequibo River drainage of Guyana.